IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DI SDN SUNGAI MIAI 5 DAN SDN SURGI MUFTI 4 DI BANJARMASIN - Hamdan Husein Batubara; Dessy Noor Ariani (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2017)
This article aims to explain the description of the implementation of school-based management in SDN Sungai Miai 5 and SDN Surgi Mufti 4 Banjarmasin. The method used is qualitative approach with descriptive type. The data sources of this research are principals and teachers. The method of data collection is interview and observation. The results of this study indicate that the implementation of school-based management at SDN Sungai Miai 5 Banjarmasin is done by involving all school residents in the planning and implementation of school programs, including parents of students. Schools have specialized staff to record and report school finances and assets. The implementation school-based manahement at SDN Surgi Mufti 4 Banjarmasin is done with the principle of togetherness, that is by drivingthe competent teachers to train less competent teachers, mobilize school entrepreneurship activities, and principals teach other teachers by providing a direct example. Thus, the implementation of school-based management requires the support of various parties for improving the learning quality in schools.Keywords: Impelementation; management based on school; MBS; elementary school